The sensitivity and specificity of the modified volume-viscosity swallow test for dysphagia screening among neurological patients - Lin, Yiqiu; Wan, Guifang; Wu, Huixiang; Shi, Jing; Zhang, Yaowen; Chen, Huayu; Wei, Xiaomei; Tang, Zhiming; Dai, Meng; Dou, Zulin; Wen, Hongmei (Frontiers in Neurology, 2022)
Oropharyngeal dysphagia (OD) is a highly prevalent condition after stroke and other neurological diseases. The volume-viscosity swallow test (V-VST) is a screening tool for OD. Considering that the recommendations of volume and thickeners in the original V-VST limited the popularization and application of the test in the Chinese population, we provide the modified V-VST to detect OD among neurological patients. In addition, the accuracy of the modified V-VST to screen OD needs to be verified. We included 101 patients with neurological diseases. OD was evaluated by modified V-VST and videofluoroscopy swallowing study (VFSS) using 3 volumes (3, 5 and 10 mL) and 4 viscosities (water, mildly thick, moderately thick, and extremely thick). In this study, to compare with the original V-VST results, a volume of 20 mL was also included. The discriminating ability of modified V-VST in detecting OD was assessed by the sensitivity and specificity values of clinical signs of impaired efficiency (impaired labial seal, piecemeal deglutition, and residue) and impaired safety of swallowing (cough, voice changes, and oxygen desaturation ≥3%) in comparison to the results of VFSS. The modified V-VST showed 96.6% sensitivity and 83.3% specificity for OD, 85.2% sensitivity and 70% specificity for impaired safety, 90.9% sensitivity and 76.9% specificity for impaired efficacy. Our study suggests the modified V-VST offers high discriminating ability in detecting OD among neurological patients.